PAPARAN TELUR CACING USUS PADA IKAN LELE YANG DIPELIHARA PADA KOLAM DENGAN SUMBER AIR DARI SUNGAI - Didik Sumanto; Juli Budi W; Sayono - (Universitas Muhammadiyah Semarang, 2008)
Background. Lele fish is the carnivore animal, and often feed w-ith feces. This habit has a risk to be a source of disease agent parasite. However, the existence of soil-transmitted-helminthes eggs in lele fish was not clear yet.Objective. To understand the proportion of infected-lele fish with the eggs of soil transmitted helmints, describe the species of them.Result. The helmipth eggs were found in 25% of lele-fish samples. The species of helminthes are Ascaris lumbricoides (80%), and mix of Ascaris lumbricoides and Tr i c hur i s tr i chi ur a (20%).Conlusion. Lele-fish were feed with feces having a risk to be a source of disease agent parasite.Keywords : soil-transmitted-helminth, lele-fi sh, Ascaris, Trichuris